2021
DOI: 10.1177/07487304211045835
|View full text |Cite
|
Sign up to set email alerts
|

Central and Peripheral Clock Control of Circadian Feeding Rhythms

Abstract: Many behaviors exhibit ~24-h oscillations under control of an endogenous circadian timing system that tracks time of day via a molecular circadian clock. In the fruit fly, Drosophila melanogaster, most circadian research has focused on the generation of locomotor activity rhythms, but a fundamental question is how the circadian clock orchestrates multiple distinct behavioral outputs. Here, we have investigated the cells and circuits mediating circadian control of feeding behavior. Using an array of genetic too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…This result is particularly striking for flies in which we monitored fat body luciferase signals while selectively expressing Clk DN within these cells (Figure 6). As these flies retain feeding rhythms (Xu et al, 2008; Fulgham et al, 2021), the results help to rule out the possibility that luciferase rhythms arise secondary to rhythmic consumption of luciferin-containing food.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This result is particularly striking for flies in which we monitored fat body luciferase signals while selectively expressing Clk DN within these cells (Figure 6). As these flies retain feeding rhythms (Xu et al, 2008; Fulgham et al, 2021), the results help to rule out the possibility that luciferase rhythms arise secondary to rhythmic consumption of luciferin-containing food.…”
Section: Discussionmentioning
confidence: 89%
“…To-GAL4 is relatively selectively expressed in the fat body (Dauwalder et al, 2002), a peripheral metabolic tissue that functions similar to mammalian liver and adipose tissue, with some additional expression in other parts of the gastrointestinal tract (Xu et al, 2008). We were particularly interested in the effect of constant environmental conditions on fat body circadian clock activity, as it has been previously reported that per expression in the abdomen of Drosophila quickly dampens in DD based on experiments conducted with a lucifierase reporter (Stanewsky et al, 1997), RNA extraction (Xu et al, 2011), or antibody staining (Fulgham et al, 2021), suggesting that fat body clocks are not sustained without light cues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolic gene regulatory network that we identified, and expression changes of fit, suggest that the fat body clock is altered in response to SP. The fat body clock regulates feeding behavior and glucose metabolism, but synchronization between the fat body clock and the clock in neuronal cells is important, and desynchronization has been shown to negatively impact egg laying (Zheng and Sehgal 2008;Fulgham et al 2021;Erion et al 2016;Xu et al 2011). This, in addition to the expression changes we observed in neuronal genes that follow a circadian expression pattern in virgin females (such as aru, retn, sand), indicate that circadian changes in response to SP are not likely to be limited to the fat body.…”
Section: Discussionmentioning
confidence: 99%
“…Fruit flies also feed rhythmically with a peak in the morning in light-dark cycles and early subjective day in constant conditions (Xu et al, 2008). While most of these rhythms are controlled by either peripheral clocks (Xu et al, 2008, Krishnan et al, 1999; Chatterjee et al, 2010) or central clocks (Helfrich-Forster, 1998), or both (Fulgham et al, 2021; Barber et al, 2021), whether and how food availability affects any of these rhythms is unknown.…”
mentioning
confidence: 99%